1941
DOI: 10.2134/agronj1941.00021962003300110002x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Applying Common Salt to a Muck Soil on the Yield, Composition, and Quality of Certain Vegetable Crops and on the Composition of the Soil Producing Them1

Abstract: Miller, Chemical Section; the assistance of Miss L. I. Butler, Miss H. M. Robinson, H. 0. Allen, and J. R. Lewis, Analytical Staff, Chemical Section, in making the mineral analyses; of the U. S. Dept. of Agriculture sugar laboratory a t Michigan State College in making the sugar determinations; and of N. K. Ellis and G. D. Sherman, Soils Department, in the field experiments. Wgures in parenthesis refer to "Literature Cited", p. 979. 4Additional studies made on the more peaty types of soils show that the conclu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
14
0

Year Published

1942
1942
1965
1965

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 0 publications
0
14
0
Order By: Relevance
“…The fact that plants could grow perfectly well in a culture miiediumii entirely lacking in sodium doubtless caused the assumption that the plants would not utilize it. Work carried on simultaneously with the present work, however, and published elsewhere (16) …”
Section: Materials and General Methodsmentioning
confidence: 80%
“…The fact that plants could grow perfectly well in a culture miiediumii entirely lacking in sodium doubtless caused the assumption that the plants would not utilize it. Work carried on simultaneously with the present work, however, and published elsewhere (16) …”
Section: Materials and General Methodsmentioning
confidence: 80%
“…Direct effects of Na on sugar beet growth in field experiments have been reported for muck soils by Harmer and Benne (9) and Harmer et al (10), for sand cultures by Tullin (32), and for table beets in pot experiments with soils by Larson and Pierre (18). Sodium deficiency symptoms have been reported (32) or described (9) in only a few instances and so far no specific function of Na, not performed by K, has been recorded (17,19). Yet for the beet, "sodium may almost be deemed an indispensable nutrient element, approaching potassium in importance" (19).…”
mentioning
confidence: 74%
“…When plants are high in K, Na responses have been observed (12,18,31) but most often these are much reduced or not at all in evidence (4,17,18,22,35). Direct effects of Na on sugar beet growth in field experiments have been reported for muck soils by Harmer and Benne (9) and Harmer et al (10), for sand cultures by Tullin (32), and for table beets in pot experiments with soils by Larson and Pierre (18). Sodium deficiency symptoms have been reported (32) or described (9) in only a few instances and so far no specific function of Na, not performed by K, has been recorded (17,19).…”
mentioning
confidence: 91%
See 1 more Smart Citation
“…Few studies have been made on environmental effects on sodium absorption since sodium is not considered essential for growth, although it has been proven beneficial in some plants (6,7). The Foods and Nutrition Department of the University of Hawaii, as early as 1937, reported that papayas grown in littoral regions not only had a salty taste, but a higher chloride content than those grown some distance from the sea (11).…”
mentioning
confidence: 99%